THE EFFECTS OF ORGANIZATIONAL CULTURE AND INDIVIDUAL CAPACITY ON BUDGETARY SLACK USING PARTICIPATIVE BUDGETING AS MODERATING VARIABLE AT IBI DARMAJAYA LAMPUNG - Pebrina Swissia (Prosiding International conference on Information Technology and Business (ICITB), 2015)
This research discusses the effects of organizationalculture and individual capacity on budgetary slack usingparticipative budgeting as moderating variables that areorganizational commitment, organizational culture andindividual capacity. The respondents chosen were basedon structural position in IB Darmajaya as 53 respondents.The data collected through survey method in the form ofquestionnaire also measuring the reliability test on allvariables and correlation analysis.The result of the research based on correlation analysisindicates the correlation level where the correlationanalysis of all variables indicates the strong level ofcorrelation. In addition, the participative budgetingpositively affects budgetary slack. On the contrary,organizational commitment and organizational cultureweakened the correlation between participative budgetingand budgetary slack. Besides, high or low individualcapacity is not able to moderate the correlation.KEY WORDS : Budgetary Slack, OrganizationalCulture, Participative Budgeting